9x-6=x+8

Simple and best practice solution for 9x-6=x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-6=x+8 equation:



9x-6=x+8
We move all terms to the left:
9x-6-(x+8)=0
We get rid of parentheses
9x-x-8-6=0
We add all the numbers together, and all the variables
8x-14=0
We move all terms containing x to the left, all other terms to the right
8x=14
x=14/8
x=1+3/4

See similar equations:

| 1/3=x/3-9 | | 9x+12=119 | | -(7x-4x=9) | | 7x+2=3x+68 | | .25x+12=6.25x | | 2(3-x)-6=-5 | | .25x+12=6.35x | | 24+x=81 | | 8x+3+2x=23 | | 2(x-(2x+16)+15)=2(x+1) | | -5x–8=12 | | 2n+5/(-3)=-1 | | -1/6=-1/3p+2/3 | | 7/8(6x−10)=−9 | | w-35=70 | | |2+2x|=5 | | -1/3(-9x+3)=17 | | 4x+8+13x=11+6x+2+x | | 5x-1=20-2 | | 0=-16t^2+36×t+0 | | 6.3-2.5=n | | -5x-(7-4-x)=-2(3x-4) | | -7x+12x+10x—-16=-14 | | 8y×2=72 | | 107-41=n | | 59049=3^n | | −4(z−12)=42 | | 3m-2(4m+5)=10+5m | | 5x+(−11)=34 | | .5y−8=−10 | | 2x+14=x+32 | | 42=17x+8 |

Equations solver categories